Pengaruh Psikospiritual terhadap Kualitas Hidup Pasien yang Menjalani Terapi Hemodialisa - Erfan Rofiqi; Nabila Shofwatul Rana; Nugroho Ari Wibowo; Septian Galuh Winata (The Indonesian Journal of Health Science, 2025)
To determine the effect of psychospiritual intervention in the form of dhikr therapy on the quality of life of patients undergoing hemodialysis therapy. This study used a pre-experimental quantitative design with a one group pretest-posttest approach. The sample consisted of patients with CKD who met the inclusion criteria and underwent routine hemodialysis therapy. The intervention in the form of dhikr therapy was given within a certain period. The data collection instrument used the WHOQOL-BREF questionnaire. Data analysis was performed using the Wilcoxon Signed Rank Test.There was an increase in quality of life scores in patients after being given dhikr therapy. The statistical test results show a significance value of p < 0.05, which indicates a significant effect of psychospiritual therapy on the patient's quality of life.Dhikr therapy as a form of psychospiritual intervention is proven to improve the quality of life of hemodialysis patients. Therefore, this intervention is recommended as a complementary approach in nursing practice to improve patient well-being.